WEARABLE HEALTH TECHNOLOGIES AND THE MEDICALIZATION OF EVERYDAY LIFE: A SOCIO-MEDICAL REVIEW - Maria Sierant; Malwina Kwaśniewska; Kamila Zmysłowska; Adam Hajdaniak; Jan Mateusz Kiersztyn; Aleksandra Grabowska; Natalia Seńcio; Anna Szatkowska; Klaudia Aleksandra Stadnik (International Journal of Innovative Technologies in Social Science, 2026)
Consumer wearable technologies have evolved from simple activity trackers into multisensor systems that continuously measure physiological and behavioural signals, generating algorithmic assessments of cardiac rhythm, sleep, recovery, stress, and metabolic responses. This trajectory increasingly blurs the boundary between wellness products and medical devices. This narrative socio-medical review examines how wearable health technologies contribute to the medicalization of everyday life by transforming ordinary activities into quantifiable indicators classified as normal, suboptimal, or potentially requiring intervention. Particular attention is given to digital medicalization, the Quantified Self, algorithmic norms, anticipatory risk, responsibilization, patient-generated health data, and the commercial circulation of bodily information. Through a synthesis of clinical and socio-ethical literature, we evaluate the dual nature of wearable tracking. While wearables may support prevention, self-knowledge, chronic-disease management, symptom documentation, and active healthcare participation, continuous monitoring can also intensify health anxiety, encourage compulsive checking, generate false alerts, and reproduce social or algorithmic inequalities. Their ultimate impact depends on device validity, design assumptions, business models, regulatory frameworks, clinical context, and individual user vulnerabilities. The challenge is not to reject digital health monitoring, but to develop technologies and governance practices that support care and autonomy without converting every bodily variation into a medical problem.